(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: Evaluate the results of treatment for ureteral stones middle 1/3 and lower 1/3 by retrograde lithotripsy using heavy Holmium laser power at Thai Binh Medical University Hospital. Methods: Cross-sectional descriptive study of 73 patient underwent ureteral lithotripsy middle 1/3 and lower 1/3 using the internal countercurrent lithotripsy method using Holmium laser energy at Thai Binh Medical University Hospital from January 2021 to June 2023. Recording data on disease characteristics; ureteral stone dissolution time; complications and outcomes. Results: The average age was 54,4±11,43 years old, men accounted for 64.4%, women accounted for 35.6%. Dull pain in the lumbar region and renal colic are the main reasons why patients go to the hospital (accounting for 57.6%). Most patients have stone dissolution time <60 minutes. Low complication rate: 13.6% had ureteral mucosal damage, 15% had complications after lithotripsy. The successful lithotripsy rate is 95.8%. Conclusion: Endoscopic retrograde laser lithotripsy is a minimally invasive, safe, and effective intervention method in the treatment of middle and lower 1/3 ureteral stones.